Forearm reconstruction with acellular dermal matrix after giant plexiform neurofibroma excision: case reports - Eduardo Madalosso Zanin; Daniele Walter Duarte; Ciro Paz Portinho; Nicolas Endrigo Arpini; Mônica Jimenez Zerpa; João MAximiliano; Antonio Carlos Pinto Oliveira; Marcus Vinicius Martins Collares (Revista Brasileira de Cirurgia Plástica)
Introduction: Giant plexiform neurinoma is a neuroectoderm and inherited disease. It is an uncommon skin tumor associated with NF1, characterized as a benign peripheral nerve sheath tumor surrounding multiple nervous fascicles. The goals of forearm coverage reconstruction are to protect the structures running to the wrist and hand and prevent scarring that leads to movement loss. Both forearm and hand play functional and social roles. Successful management of complex wounds is necessary for the overall functional rehabilitation of these patients. Case Report: A 31-year-old woman presented at the plastic surgery division with a giant plexiform neurofibroma in the right forearm. After careful resection, all anterior forearm tendons were exposed. The defect was covered with graftable Pelnac T (thickness of 3mm and sizing 12 X 24cm2), fixed with 4-0 monocryl sutures. After 10 days, the acellular dermal matrix silicone layer was removed, and a split-thickness skin meshed graft was placed. On day 7, the acellular dermal matrix showed good signs of intake. On day 17, we observed a 95% graft survival. At the 3-month follow-up, reconstruction was stable without contouring defects, the hand had full range of motion, and the patient had no problems in daily activities. Conclusions: Acellular dermal matrix appears to be a useful option in covering complex defects in the forearm, allowing for less morbidity and rapid functional recovery.